Computer and template assisted orthopedic surgery - Konermann, Werner; Haaker, Rolf (Springer Berlin Heidelberg, 2013)
Computer-assisted surgery is a growing sub-discipline of orthopaedic surgery. This book offers a comprehensive presentation of scientific work and clinical experience including new technologies like individual templating in unicompartmental and total knee arthoplasty based on computer-assisted design technology. Computer-assisted surgery involves not only total knee and total hip arthroplasty, but also trauma, sports and revision surgery. In this edition we have added sections on 3D fluoroscopy-based spinal surgery as well as 3D fluoroscopy-based trauma surgery. Even in total hip surgery, navigation systems offer exciting new aspects, and the clinical benefit of navigation in total knee arthroplasties has now been demonstrated. We believe that this textbook will be of interest to those new to this specific field, while also providing an update for experienced users. An added benefit is the international character of this textbook, including experiences from Switzerland, Israel, the United States and the German-speaking countries.